Compound Chinese herbal medicine feed additive capable of improving growth speed of golden pompanos and preparation method of compound Chinese herbal medicine feed additive as well as feed adopting additive - LIANG CHAO; ZHANG HAITAO; WANG ZHUODUO; WANG TUO; SUN GUANGWEN; WEI ZHENNA; JIANG YONGJIE; LIANG HAIOU (2016)
The invention discloses a compound Chinese herbal medicine feed additive capable of improving the growth speed of golden pompanos. The compound Chinese herbal medicine feed additive is prepared from the following components in percentage by mass: 8 percent to 12 percent of radix polygoni multiflori, 13 percent to 18 percent of radix codonopsis, 8 percent to 14 percent of fructus schisandrae chinensis, 6 percent to 12 percent of medicated leaven, 5 percent to 8 percent of fructus crataegi, 3 percent to 5 percent of fructus cnidii, 17 percent to 22 percent of white peony root, 12 percent to 15 percent of Chinese angelica, 5 percent to 10 percent of tangerine peel, 3 percent to 5 percent of vitamin C, 1 percent to 2 percent of methionine, 1 percent to 2 percent of inositol and 1 percent of astaxanthin. According to the additive disclosed by the invention, the digestion and absorption capability of the golden pompanos can be improved, the conversion rate of golden pompano feed is increased, and the growth speed o